Factory Layout Redesign With Lean Manufacturing And Simulated Annealing Algorithm At PT. XYZ - Tengku Putri A (Journal Basic Science and Technology, 2020)
PT. XYZ is a manufacturing company in the field of wood processing that produces furniture products and raw materials for rambung. On the production floor of PT. XYZ there is a buildup of materials during the production process. This stacking process does not add value. This results in delays for the next process or can be called waste of delay. Another problem is the backflow of material transfer (backtracking) where the movement of the material flow through several stations affects the completion of the product. In solving these problems, a lean manufacturing approach is used to identify and reduce activities that do not add value during the production process and shorten lead times. The simulated annealing algorithm method is used to fix the backflow problem on the layout of the production floor at PT. XYZ. The results showed that there was a decrease in the displacement moment of 43.44%, an increase in production capacity with an actual process cycle efficiency of 44.98% with an average production of 48 units/day and a proposed process cycle efficiency of 63.91% with an average production - an average of 63 units / day after repairs with lean manufacturing.